Risk Factors and Clinical Outcomes of Recurrence in Adult Ovarian Granulosa Cell Tumors - Golmohammadi Tavallaee, Mansoureh; Hasanzadeh Mofrad, Malihe; Yousefi, Zohreh; Mottaghi, Mansoureh; Homaei Shandiz, Fatemeh; Davachi, Behrouz; Hamidi, Bahram; Farazestanian, Marjaneh; Afzaljavan, Fahimeh (Cancer reports, 2024)
ABSTRACT Purpose Granulosa cell tumors (GCTs) of the ovary are rare but clinically significant malignancies. Despite advances in treatment, recurrence has remained a substantial challenge. This study aimed to identify clinical outcomes and potential prognostic risk factors for recurrence in patients diagnosed with GCTs. Methods In a retrospective cohort study, the ovarian cancer database of the gynecological tertiary referral cancer center, Mashhad University of Medical Sciences, Mashhad, Iran, was searched from August 2012 to August 2023 to find GCT cases. Demographic, clinical, pathological, intervention‐related factors, follow‐up, and survival findings were meticulously collected. Data were analyzed using SPSS v 23. Results Ninety‐two patients with GCTs, including 86 AGCT and 6 JGCT subjects, were identified. Based on further analysis of AGCT patients, most patients were ages under 50 (58.1%), clinically presented pain (32.6%), and abnormal uterine bleeding (27.9%) as the most frequent symptoms. Stages IA (64.0%) and IC (20.9%) were common. Five‐year overall and progression‐free survival were 98.2% and 90.8%, respectively. With a median follow‐up time of 72 (0.0–180) months, disease recurrence was observed in 19 patients (23.9%), and five patients (5.4%) died of the disease. Stage IV was a hazard factor of recurrence (HR = 7.62, 95%CI (1.89–30.63); p = 0.004). Conclusions The present study provides valuable insights into the outcomes and potential risk factors for recurrence in ovarian AGCTs. It duplicates the importance of stage in the prognosis of AGCT patients and highlights the safety of fertility‐sparing surgery in stage I and the lack of need to administer chemotherapy in stage IC.